King Tutankhamun tells all! - Naunton, Chris 1978- (Thames & Hudson, 2021)
Young history buffs and celebrity fanatics alike will enjoy this humorous and irreverent introduction to King Tutankhamun written by Egyptologist and TV presenter Dr Chris Naunton. Readers hear first-hand from King Tutankhamun how he became the ruler of ancient Egypt at the tender age of nine, and what it was like to be rudely awakened from the afterlife by British Egyptologist Howard Carter in 1922
Includes index
Keywords: Tutankhamen / King of Egypt / Juvenile literature; Egypt / History / Eighteenth dynasty, ca. 1570-1320 B.C. / Juvenile literature; Pharaohs / Biography / Juvenile literature; Tutankhamen / King of Egypt; Égypte / Histoire / ca 1570-1320 av. J.-C. (XVIIIe dynastie) / Ouvrages pour la jeunesse; Pharaons / Biographies / Ouvrages pour la jeunesse; Pharaohs; Egypt; 1570-1320 B.C.; Biography; picture books; Picture books; Creative nonfiction; Biographies; History; Juvenile works; Essais fictionnels; Livres d'images; Sachbilderbuch; Kindersachbuch